The effect of cardiac rehabilitation on quality of life in patients with acute coronary syndrome - Asghar Khalife-Zadeh; Safoura Dorri; Saeed Shafiee (Wolters Kluwer Medknow Publications, 2015)
Background: Acute coronary syndrome is one of the major cardiovascular diseases that leads to a significant amount of morbidity. The purpose of the present study was to investigate the effect of cardiac rehabilitation on quality of life in patients with acute coronary syndrome. Materials and Methods: This was a clinical trial study conducted on 50 patients with acute coronary syndrome admitted to the coronary care units of Shohada Hospital in Isfahan in 2013-2014. The participants were randomly assigned to control (n = 25) and study (n = 25) groups. The study group received cardiac rehabilitation in phase 1 and 2. Phase 1 was conducted in a hospital in Isfahan province that had no cardiac rehabilitation center but had minimal cardiac rehabilitation equipments. Phase 2 was conducted at home by follow-up through telephone and referring the patients to the hospital. The control group received usual cardiac rehabilitation. The data were collected via a demographic questionnaire and SF-36 quality of life questionnre before and 1 month after intervention by the researcher. Data were analyzed by independent samples t-test. Results: In the study group, the mean scores in all domains of quality of life increased significantly after intervention (P < 0.05). In the control group, the mean scores of quality of life were not significantly different before and after intervention (P > 0.05). A significant difference was found between the study and control groups in all domains of quality of life except for general health and social function (P < 0.05) in favor of the study group. Conclusions: The results of this study showed that cardiac rehabilitation program could lead to improving the quality of life in the patients with acute coronary syndrome.